2020
DOI: 10.4102/ajod.v9i0.766
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, disability and the context of healthcare triage in South Africa: Notes in a time of pandemic

Abstract: During disasters, when resources and care are scarce, healthcare workers are required to make decisions and prioritise which patients receive life-saving resources over others. To assist healthcare workers in standardising resources and care, triage policies have been developed. However, the current COVID-19 triage policies and practices in South Africa may exclude or disadvantage many disabled people, especially people with physical and intellectual impairments, from gaining intensive care unit (ICU) access a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 36 publications
1
56
0
3
Order By: Relevance
“…In residential care settings, shielding and self-isolation were difficult during the first wave of the pandemic. This was due to the: initial unpreparedness of the facilities at the pandemic outset, shared use of essential living spaces, crowding and shared rooms, proximity to other residents, residents’ difficulty understanding new rules imposed suddenly, difficulty in maintaining standards of hygiene during home visits, multiple shift staffing patterns, staff working in multiple settings, and high levels of personal care assistance required from staff (e.g., with eating, toileting, or transferring from bed to wheelchair) [ 16 , 30 , 31 , 36 , 38 , 39 , 43 , 51 , 53 , 54 , 59 , 70 , 78 ]. Indeed, stemming from the latter reason, many articles pointed out that a wide range of people with disabilities who rely on assistants for basic activities of daily living have greater risks of infection [ 6 , 32 , 36 , 41 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In residential care settings, shielding and self-isolation were difficult during the first wave of the pandemic. This was due to the: initial unpreparedness of the facilities at the pandemic outset, shared use of essential living spaces, crowding and shared rooms, proximity to other residents, residents’ difficulty understanding new rules imposed suddenly, difficulty in maintaining standards of hygiene during home visits, multiple shift staffing patterns, staff working in multiple settings, and high levels of personal care assistance required from staff (e.g., with eating, toileting, or transferring from bed to wheelchair) [ 16 , 30 , 31 , 36 , 38 , 39 , 43 , 51 , 53 , 54 , 59 , 70 , 78 ]. Indeed, stemming from the latter reason, many articles pointed out that a wide range of people with disabilities who rely on assistants for basic activities of daily living have greater risks of infection [ 6 , 32 , 36 , 41 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Globally, another analysis showed that pages of the World Health Organization’s website, March–May 2020, were only 60% compliant regarding web accessibility guidelines [ 75 ]. Additionally, people with sensory processing and visual impairments may need to rely or depend on touch and tactile senses for stimulus or to perform their routine activities or outdoor movement, and thereby face greater infection risks [ 33 , 38 , 40 , 43 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…What the COVID-19 pandemic has revealed all too starkly is the hidden political and social prejudices that endure within modern health systems, [48] in which selective care is dispensed mainly for profit at the expense of the socially vulnerable.…”
Section: In Practicementioning
confidence: 99%